Discussion Of Papers Presented At Chicago And New York Meetings Discussion Of Papers Presented At Chicago And New York Meetings Discussion Of Papers Presented At Chicago And New York Meetings (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
P. H. ARGALL, Magdalena, N. Mex. (written discussion *).-The Chilean mill has generally been considered a fine-crushing machine and as such has had many advocates; it has also. had quite a number of denouncers; hence, the action of the Portland engineers in using the Chilean mill for the preparatory work usually accomplished in, rolls or rock breakers and adding a ball mill to do the fine grinding is novel, though of doubtful utility in the long run, even though a fair efficiency is obtained for the combination machines, as measured by Chilean mill practice. In order to follow the development of Chilean mill practice on Cripple Creek ores, I might say that two 6-ft., Chilean mills were placed in operation in Stratton's Independence mill in April, 1908, treating ore crushed by rolls to pass Y4 in. screen aperture. Screening was, however, found to be an unnecessary refinement, as was also the use of plows in the mills; both screening and plowing were abandoned before the Portland engineers finished the experiments in stamp milling upon which they were then engaged. Two additional 6-ft. Chilean mills were added in the spring of 1911, three of them giving the required 10,000 tons per month capacity, one being always in reserve. The Portland company began using Chilean mills in June, 1910, at its Victor mill, and the same company purchased the Stratton's Independence mill in June, 1915, and remodeled it; it is now known as the Independence mill. A description of Stratton's Independence milling practice, is given in the November, 191.1, issue of Mining Majazine (London). These Chilean mills were used as fine grinders and that they accomplished their purpose is shown by the screen analyses, in which 62 per cent. of the pulp passed 150-mesh screens. To make coarse crushers of these Chilean mills, the Portland engineers have increased the speed, substituted steel in various parts for cast iron, provided new and enlarged thrust bearings to take care of the centrifugal force incident to higher speed, and have, thereby, greatly increased the cost of the machines. They have also reduced the width of the tires and dies from 8 in., as used in the original mill, to 7 in., a reduction of 12 ½ per cent. in the crushing surfaces, to say nothing of the loss of abrasion or attrition incident to the larger surface. At the same time, they have apparently increased the weight of the rollers by using tires 5 7/8 in. thick as against tires varying between 3 and 4 in. on the original mills, thereby increasing